Clinical characteristics and long-term survival differences of the ANCA-associated vasculitis group: a cross-sectional study of 27 patients - Dadonienė, Jolanta; Kumžaitė, Gintarė; Mačiulytė, Rimvydė; Miltinienė, Dalia (Acta medica Lituanica, 2017)
Objective. The goal of this study was to describe long-term patient survival and possible prognostic factors of a  group of patients diagnosed with granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) hospitalized at the  tertiary Rheumatology Centre in Vilnius. Material and Methods. A cross-sectional study of 27 patients hospitalized at the Rheumatology Centre of Santaros klinikos of Vilnius University Hospital from 1  January 2001 to 31  December 2015 with diagnoses of GPA and MPA were carried out. Data on demographics, clinical characteristics, laboratory data, and the Birmingham Vasculitis Activity Score were collected. Results. Seven (25.9%) patients during the  onset of the  disease received only oral glucocorticoids and 20 (74.1%) patients took additional medication. The BVAS median was 7 (minimum [min] – 2; maximum [max] – 23). The age median was 52 years (min  –  12; max  –  75). The  overall mortality rate was 18.5%. Mean survival time was 126.6 months (95% confidence interval [CI] = 104.5 to 148.6) limited to 154.6 months for the longest-surviving patient. Conclusions. Life expectancy during past 15  years for AAV patients increased from 99.4 to 126.6 months. A high BVAS score at the  onset of the  disease is a  bad prognostic factor related to shorter life expectancy. The growth of Staphylococcus aureus from nasopharynx might be associated with higher mortality rates and relapses in AAV patients.
Keywords: ANCA-associated vasculitis; outcomes; microscopic polyangiitis; granulomatosis with polyangiitis; BVAS score; life expectancy